DETERMINAN PENDAPATAN USAHATANI ALPUKAT DAN KONTRIBUSINYA TERHADAP PENDAPATAN RUMAHTANGGA PETANI DI KAWASAN GEOPARK RINJANI - Septiadi, Dudi; Yusuf, Muhammad (JURNAL AGRITA, 2024)
Pringgasela District is one of the avocado producing areas in the Rinjani Geopark Area, East Lombok Regency. Located 19 km west of the city center of East Lombok Regency. The purpose of this research is to (1) analyze the factors that influence the income of avocado farmers in Pringgasela District. (2) analyze the contribution of avocado farming income to farmer household income in Pringgasela District; The method used in this research is a quantitative-descriptive method. The unit of analysis used in this research is farmers who cultivate avocados in Pringgasela District, East Lombok Regency in 2024. The primary data collection method was carried out through direct observation using a questionnaire for 41 farmers as respondents. The technique for collecting respondent data was carried out by accidental sampling. The research results show that: factors that influence the income of avocado farmers are the amount of production, production costs and the age of avocado farmers. The contribution of avocado farming to farmer household income is 10.48%. Avocado cultivation in the Mount Rinjani geopark area pays attention to sustainability aspects by not using chemical fertilizers in farming activities.